Increased Vulnerability to Pattern-Related Visual Stress in Myalgic Encephalomyelitis. (December 2015) - Wilson, Rachel L.; Paterson, Kevin B.; Hutchinson, Claire V.
The objective of this study was to determine vulnerability to pattern-related visual stress in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). A total of 20 ME/CFS patients and 20 matched (age, gender) controls were recruited to the study. Pattern-related visual stress was determined using the Pattern Glare Test. Participants viewed three patterns, the spatial frequencies (SF) of which were 0.3 (low-SF), 2.3 (mid-SF), and 9.4 (high-SF) cycles per degree (c/deg). They reported the number of distortions they experienced when viewing each pattern. ME/CFS patients exhibited significantly higher pattern glare scores than controls for the mid-SF pattern. Mid-high SF differences were also significantly higher in patients than controls. These findings provide evidence of altered visual perception in ME/CFS. Pattern-related visual stress may represent an identifiable clinical feature of ME/CFS that will prove useful in its diagnosis. However, further research is required to establish if these symptoms reflect ME/CFS-related changes in the functioning of sensory neural pathways.